Purses, bags & totes (American Quilter's Society, 2012)
"Create bags, purses, and totes in no time! Sew any of the 10 projects: Handbags, Messenger bags, Shoulder bags, Backpacks, Eco bags, Tote bags. The book includes easy-to-follow instructions plus full-size patterns on the CD for no fuss construction. Great for gifts, too"--